2023
DOI: 10.3390/vaccines11020247
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Repeated Adverse Effects following Booster Dose of mRNA COVID-19 Vaccine: Results from the MOSAICO Study

Abstract: The successful deployment of safe and effective vaccines against coronavirus disease 2019 (COVID-19) has been crucial in reducing the global disease burden. Owing to the need for vaccination series over time, continuous observational studies are needed to estimate the COVID-19 vaccine response in real-world conditions. In particular, the detection, assessment, and understanding of adverse effects following immunization (AEFI) with a COVID-19 vaccine are crucial to better address vaccination strategies. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Our study showed that the most frequent adverse effects were pain at the injection site, fatigue, muscle pain, swelling at the injection site, headache, fever and chills. These findings are in accordance with the literature regarding the adverse effects of the first booster dose [1418,22,23]. Moreover, a recent systematic review investigated the prevalence of adverse effects after the primary COVID-19 vaccine doses and found that the most frequent adverse effects among 10,632 participants were pain at the injection site (77.3%), muscle pain (39.7%), swelling at the injection site (34%), headache (33.3%), chills (18.3%), fever (18%), swollen lymph nodes (8%), nausea (7.9%), and shortness of breath (7.6%) [11].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our study showed that the most frequent adverse effects were pain at the injection site, fatigue, muscle pain, swelling at the injection site, headache, fever and chills. These findings are in accordance with the literature regarding the adverse effects of the first booster dose [1418,22,23]. Moreover, a recent systematic review investigated the prevalence of adverse effects after the primary COVID-19 vaccine doses and found that the most frequent adverse effects among 10,632 participants were pain at the injection site (77.3%), muscle pain (39.7%), swelling at the injection site (34%), headache (33.3%), chills (18.3%), fever (18%), swollen lymph nodes (8%), nausea (7.9%), and shortness of breath (7.6%) [11].…”
Section: Discussionsupporting
confidence: 93%
“…Literature supports this finding since two other studies found that all participants had adverse effects after the first booster dose [20,21]. Other studies found also high prevalence of adverse effect after the first booster dose ranging from 74.7% to 89% [14][15][16][17]22,23]. Slight differences in prevalence of adverse effects among studies could be attributed to different study designs, populations, and definitions.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations